Effect of trace elements and nutrients on 21 autoimmune diseases: a Mendelian randomization study - Jia, Ming-Jie; Yin, Hua-Fang; Liang, Ying-Chao; Jiang, Feng; Li, Hui-Lin (Frontiers in Immunology, 2025)
BackgroundNumerous clinical studies have observed a close relationship between serum trace elements, nutrients, and autoimmune diseases. However, whether there is a genetic causal effect between serum trace elements, nutrients, and autoimmune diseases remains unclear.ObjectiveThis study aims to investigate the causal effects of serum trace elements and nutrients on 21 autoimmune diseases using Mendelian randomization (MR).MethodsSingle nucleotide polymorphisms for the exposure factors (serum trace elements and vitamins) were obtained from the published UK Biobank database and genome-wide association study (GWAS) public databases. Outcome GWAS data were derived from the FinnGen database. MR was employed to explore the causal relationships between 9 trace elements and 6 vitamins and autoimmune diseases. Causal inference was performed using inverse variance weighted methods, MR Egger, and weighted median methods. Subsequently, heterogeneity tests, horizontal pleiotropy tests, MR-PRESSO tests, and leave-one-out analyses were conducted for sensitivity analysis to evaluate the robustness of the study results. Finally, trace elements and vitamins that were statistically significant in the IVW method and had consistent effect sizes and odds ratios across five methods were selected as exposure factors with a causal relationship to diabetes and its complications. Additionally, multivariable Mendelian randomization was employed to assess the combined effects of multiple exposure factors on autoimmune diseases.ResultsMR analysis indicated that elevated levels of the trace element copper were associated with an increased risk of systemic lupus erythematosus (SLE) and a decreased risk of ulcerative colitis. Carotene was found to have a negative causal relationship with adult-onset Still’s disease (AOSD). Elevated levels of copper and selenium were associated with an increased risk of autoimmune hyperthyroidism. Calcium levels showed a negative causal relationship with the risk of polyarteritis nodosa. MVMR results demonstrated that selenium could independently affect the risk of autoimmune hyperthyroidism, separate from copper.ConclusionThe findings from both univariable and multivariable Mendelian randomization studies support a causal relationship between trace elements, nutrients, and autoimmune diseases. These results have significant clinical implications for developing targeted prevention and treatment strategies for autoimmune diseases.